Penelitian pengaruh cuaca terhadap perubahan sifat tegangan putus dan perpanjangan putus berbagai jenis kulit - Rumiyati, V Sri Pertiwi; Musthofa, Hadi (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1994)
The objective of the research is to find out the effect of weathering exposure on quality of leather by WeathepOmeter apparatus. During in door test by weather - Ometer, the condition of research is kept constanly i.e black panel at 45oC, dry bulb at 36oC, wet bulb at 26oC and humidity at 45%, specimen exposed taking over from the chamber for testing purpose were caried out every 25 hours and performed up to the limiting time at whice tensile strength and elongation at break properties change.